Perilaku Bertanggung Jawab Generasi Milenial di Destinasi Pariwisata Halal: Sebuah Tinjauan Literatur - Sukmana, Eman (JURNAL NASIONAL PARIWISATA, 2025)
This research seeks to analyse the relationship between halal tourism and millennial tourists' attitudes and behaviour, as well as to explore the relationship between Islamic and sustainability principles that influence the formation of responsible behaviour among millennial tourists. This research uses a descriptive analysis approach to qualitative data based on the results of a systematic literature review. A total of 45 scientific articles from reputable journal databases (Scopus, World of Science, Google Scholars, Crossref, DOAJ, and Semantic) were collected using Mendeley software to be examined based on the identification of their frameworks and concept maps. This study has proposed a new concept map that is interesting for further research, namely that the experience of travelling to destinations labelled as halal tourism influences the formation of responsible behaviour, based on the application of Islamic principles and sustainability. Unfortunately, this study is still limited to a systematic literature review focusing on the analysis of 45 scientific articles, as well as being limited to the context of the millennial generation and halal tourism in Indonesia. Therefore, the relationship between halal labelling and the responsible behaviour of millennial tourists in tourist destinations that are in line with Islamic values and sustainability still needs to be followed up with further research.